The light between oceans [videorecording (DVD)] - Cianfrance, Derek; Stedman, M. L.; Fassbender, Michael, 1977-; Vikander, Alicia, 1988-; Weisz, Rachel, 1970- (Touchstone Home Entertainment : DreamWorks Pictures, 2017)
A lighthouse keeper, living off the coast of Australia with his wife, finds a baby on an adrift rowboat. They rescue and raise the child as their own, changing their lives and that of a stranger.